Retos éticos y límites de la RRI para mejorar los procesos de gobernanza de la investigación y la innovación - Von Schomberg, René; González Esteban, Elsa; Sanahuja-Sanahuja, Rosana (RECERCA. Revista de Pensament i Anàlisi, 2022)
Responsible research and innovation (rri) imposes normative requirements on research and innovation processes resembling three successive steps, each more ambitious than its predecessor, with distinct features. For the research dimension the distinct features reflect the normative requirements of, first, credible research (through, for example, codes of conduct and standards for scientific integrity); second, responsive research (by opening up science to societal demands); and third, responsible research (which includes the anticipation of socially desirable outcomes). Equally distinct features reflect the requirements of credible innovation, responsive innovation, and responsible innovation (Von Schomberg, 2019).